PEMBUATAN ALAT PENGERING BIJI JAGUNG DENGAN SISTEM UNGGUN BERGERAK DAN KONDISI OPTIMAL DARI PENGERINGAN - Rambe, Siti Masriani (Jurnal Dinamika Penelitian Industri, 2010)
The research has been conduected dryer of corn with fluidized bed system and stainless stel material of tank. Tank was equipment with a strirer 100 rpm, blowers, and theÂ  thermometer as a temperature controller. The tool is made to be dry material of corn wrhre corn has moisture high initial levels of 40%. Influence the feed of materials and temperature of drying seed corn by the countercurrent flow of heat sources, where the material flows from the top of the tank while the drying air flow from under the tank flows.this drying process varied with a capacity of 15 kg/hr ; 17,5kg/hr and 20kg/hr attemperature of 50oC,60oC and 70oC. the results showed the best conditions in the corn kernels are drying at a temperature of 70oC for all capacity rate of the material on 15 kg/hr corn,17,5kg/hr and 20kg/hr in the water content reaches 14%, as a safe condition in seed and as storage products grains especially maize seeds.